Calculus : Early transcendentals - Howard Anton and others; Bivens, Irl; Davis,Stephen (New Delhi Wiley India Pvt Ltd, 2024)
This Indian adaptation of the book maintains those aspects of the previous editions that have led to the series being so successful. In addition to strengthening the coverage of Trigonometric and Derivative Functions, this edition includes Predator-Prey Model for mathematical modelling of differential equations. The topic of Infinite Series has also been elaborated by adding Subsequence, Bounded Sequences, and Logarithmic Test. This edition also includes multiple choice questions based on the questions from competitive examinations.
Keywords: Calculus